2020
DOI: 10.1186/s41256-020-00159-y
|View full text |Cite
|
Sign up to set email alerts
|

The need for COVID-19 research in low- and middle-income countries

Abstract: In the early months of the pandemic, most reported cases and deaths due to COVID-19 occurred in high-income countries. However, insufficient testing could have led to an underestimation of true infections in many low-and middle-income countries. As confirmed cases increase, the ultimate impact of the pandemic on individuals and communities in low-and middle-income countries is uncertain. We therefore propose research in three broad areas as urgently needed to inform responses in low-and middle-income countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 9 publications
0
66
0
Order By: Relevance
“…The challenges for modelling the effectiveness of these interventions will be enormous. In addition, these interventions were in most cases so complex that it is doubtful whether their effectiveness can be studied systematically [43,44]. Yet we were warned a few years ago in the region that "considering a public health measure with such dramatic social effects as containment, the transnational scienti c community should engage rapidly in building evidence about the e cacy of containment in the Ebola outbreak" [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges for modelling the effectiveness of these interventions will be enormous. In addition, these interventions were in most cases so complex that it is doubtful whether their effectiveness can be studied systematically [43,44]. Yet we were warned a few years ago in the region that "considering a public health measure with such dramatic social effects as containment, the transnational scienti c community should engage rapidly in building evidence about the e cacy of containment in the Ebola outbreak" [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis also highlights the challenges of the quality of these data, particularly when, for example, when deaths are not counted in communities in Guinea in a disaggregated manner, when RDTs (Rapid Diagnostic Tests) are used in Benin or when the number of tests is reduced in Senegal or Guinea. The magnitude of the pandemic is thus likely to be underestimated here, as elsewhere [44]. Access to epidemiological data, if available, will make it possible to assess excess mortality in the countries, at different territorial scales, and thus estimate whether the gures disseminated re ect the real situation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is also argued that low GDP countries may lack testing capabilities, thus underestimating COVID-19 impacts. While this may be true in the early days or months of the pandemic, testing ability has increased to levels comparable to high-income countries 15 . This study found COVID-19 deaths not signi cantly correlated with total tests carried out by countries, although understandably COVID-19 cases signi cantly correlates with testing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the resource-poor countries remain at disproportionally higher risk of disease spread internally or overseas. These countries have limited diagnostic and research capacity that could help in timely estimation of COVID-19 incidence [8,9]. Such a knowledge base is vital to guide policy makers in understanding potential impact of risk-mitigation strategies and plan accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the models' estimation addressed situations in high-income countries [19][20][21]. To date, the limited disease modelling and research capacity prevented estimation of prevalence in LMICs [8,9]. In the absence of available evidence or scientific forecasting, the resource-limited or resource-constrained settings adopt developed countries' strategies that might not be suitable for them.…”
Section: Introductionmentioning
confidence: 99%